Nominal pluralization and countability in African varieties of English - Mohr, Susanne (Routledge, Taylor & Francis Group, 2022)
"This book is the first comprehensive analysis of plural marking, its morphosyntax and semantics, in African varieties of English. Mohr explores the rich diversity in the varieties and how different conceptualizations of the number category are realised across different cultures. The investigation of unstandardized noun plurals in Kenyan, Tanzanian, Ghanaian and Nigerian Englishes is based on a mixed methods design drawing on corpus linguistics, acceptability questionnaires and psycholinguistic experiments. In this vein, the book not only contributes to the description of each of these four varieties, but also sheds light onto standardization processes and language change in New Englishes. Importantly, it is a plea for the triangulation of data and mixed methods approaches in World Englishes research, as the combination of these methods grants insight into unforeseen areas of language structures and use. This volume is a useful reference work for students and researchers in world Englishes, varieties of English and African studies as well as those interested in linguistic anthropology."
Includes bibliographical references and index
Keywords: Substantiv; Zahl; Englisch; Sprachvariante; Plural; Afrika; English language / Africa / Number; English language / Africa / Noun; English language / Variation / Africa; Africa / Languages / Influence on English